Performance standards and employee effort: Evidence from teacher absences - Seth Gershenson (W.E. Upjohn Institute for Employment Research, 2015)
The 2001 No Child Left Behind Act (NCLB) increased accountability pressure in U.S. public schools by threatening to impose sanctions on Title 1 schools that failed to make adequate yearly progress (AYP) in consecutive years. Difference-in-difference estimates of the effect of failing AYP in the first year of NCLB on teacher effort in the subsequent year suggest that, on average, teacher absences in North Carolina fell by about 10 percent, and the probability of being absent 15 or more times fell by about 30 percent. Reductions in teacher absences were driven by within-teacher increases in effort and were larger among more effective teachers.
Keywords: J45; J48; J22; I2; 330; performance standards; employee effort; teacher absences; accountability; No Child Left Behind